ANALYZING THE INCIDENCE AND RISK FACTORS OF POST-TRAUMATIC STRESS DISORDER IN FIRST RESPONDERS. - Meshael Nasser alnuwisser, Bandar Saad Alaftan, Ayed Marfo Alanazi, Maram Hussein Almowallad; Abdulrhman Abdullh Olayan Alanazi, Asma Mohammed alaenazi, Noha Abdullah Almudaymigh (Chelonian Research Foundation, 2023)
Post-traumatic stress disorder (PTSD) is a mental health condition that can develop after a person has been exposed to a traumatic event. First responders, such as firefighters, police officers, paramedics, and emergency medical technicians, are at a high risk of developing PTSD due to their exposure to distressing and often traumatic events in the line of duty. This essay aims to analyze the incidence and risk factors of PTSD in first responders. By examining current research studies and literature, this essay will explore the prevalence of PTSD among first responders, as well as the various risk factors that contribute to its development. Understanding the incidence and risk factors of PTSD in first responders is essential for the development of effective prevention and intervention strategies to support the mental well-being of these dedicated individuals. Keywords: PTSD, first responders, incidence, risk factors, trauma, mental health